Study on phytoplasma causing Napier grass stunt disease (NGSD) in different farmers’ fields in Ada Woreda, Ethiopia - Melesse, A. (Addis Ababa University, 2009)
Napier or elephant grass (Pennisetum purpureum) is a perennial grass grown widely in East Africa as a fodder crop. It is being promoted in Ethiopia for use by cut and carry (zero grazing) smallholder livestock keepers. The International Livestock Research Institute (ILRI) in Ethiopia maintains a germplasm collection of Napier at its field stations in Debre Zeit and Zewai. ILRI distributed apparently clean cuttings to the farmers, however it was only recently a disease, phytoplasma was identified in these stations. Therefore, this study was initiated to detect Napier grass stunt disease (NGSD) causing agent (Phytoplasma) and the extent of its distribution in Ada woreda through Nucleic acid spot hybridization (NASH) technique, Polymerase chain reaction (PCR) and PCR- RFLP (Restriction Fragment Length Polymorphism). A total of 603 Napier grass leaf samples from 15 farmers’ field of 5 villages, ILRI/Debre Zeit gene bank, Ethiopian Institute of Agricultural Research (EIAR/Debre Zeit) and Genesis farm were screened for the presence of phytoplasma and its symptoms. Following this the effect of cutting on the prevalence of the disease was studied on Napier grass accessions 14984, 16786, 16837 and 16835. Passive transmission of the disease was also studied in a screen house with phytoplasma inoculated plants. Out of the total samples 4.3% were phytoplasma positive and only 0.8% showed the symptom. Cutting increased the prevalence of the pathogen in all accessions, however accessions 16786 and 16835 were more affected than the others. In the screen house, symptom development was correlated with the presence of Phytoplasma in 60% of the analyzed leaf samples. Out of the 19 NASH positive samples screened for the presence of phytoplasma 18 were found to be positive by PCR. PCR- RFLP result showed that digestion with Rsa I restriction enzyme had a similar banding pattern to 16Sr XI phytoplasma group found in Kenya. Therefore, the phytoplasma identified in this study seems to differ from 16SrIII group that was previously found in Zewai and Debre Zeit ILRI fields. Therefore, this study confirmed the presence of phytoplasma infection of Napier grass in Ada woreda. Further characterization of the phytoplasma using sequence analysis is needed to specifically identify the phytoplasma group.